ANALISIS PENGELOLAAN DANA MUDHARABAH BERDASARKAN PSAK 105 PADA PADA BMT INSAN MULIA PALEMBANG - Eva Susanti (LA RIBA: Jurnal Perbankan Syariah, 2021)
This study aims to determine how the management of the Mudharbah System funds based on PSAK No. 105 on BMT Insan Mulia. This writing uses a quantitative descriptive method through observation, interviews and documentation studies. So from this research, findings indicate that the management of mudharabah funds is based on PSAK No. 105. Berkah Savings are deposits that use Mudharabah contracts, customers are not only limited to depositing funds, but also allow the BMT to manage them in order to achieve profits. The profits are divided between the BMT and the members according to the contract. The profit or profit is distributed every month according to the agreement, as for the profit-sharing ratio on Berkah deposits between customers and BMT is 10:90, Qurban deposits are deposits that use Mudharabah contracts, customers are not only limited to depositing funds, but also allow BMT to manage them in order to achieve profit. The profit is divided between the BMT and the customer according to the contract. The profit or profit is distributed every month according to the agreement, as for the profit-sharing ratio on Qurban deposits between customers and BMT is 30:70, Education Savings are deposits that use Mudharabah contracts, members are not only limited to depositing funds, but also allow the BMT to manage it in order to achieve profit. The profit is divided between the BMT and the customer according to the contract. The profit or profit is distributed every month according to the agreement, while the profit sharing ratio on Education savings between customers and BMT is 30:70, Term Deposits are deposits that use Mudharabah contracts, members are not only limited to depositing funds, but also allow BMT to manage it in order to achieve profit. Deposit funds can be withdrawn after the deposit period has expired or is due, i.e. options of 3 months, 6 months, 9 months, up to 12 months, with the profit-sharing ratio between the customer and the BMT is 40:60 (for those 3 & 6 Months) and 45:55 (for 9 and 12 Months).